Potential of Emodin as Effective Therapy Overcoming COVID-19 Through Inhibition of the SARS-CoV-2 Spike Protein Interaction on ACE2 Receptors - Ilham, Ahmad Fadhil; Handayani, Diah (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: The coronavirus disease 2019 (COVID-19) once became a major pandemic in the history of human health. Patients in severe to critical conditions, especially with comorbidities, are more likely to have complications such as ARDS, cytokine storm, higher mortality rates, and require more effective treatments. Emodin is a candidate regimen that has the potential benefit for COVID-19.Method: This literature review was synthesized with literature searches on journal databases such as PubMed, ScienceDirect, EMBASE, and the Google Scholar search engine. As a result, three main articles and 36 supporting articles were used to synthesize this literature review.Results: The pathogenesis of SARS-CoV-2 infection was similar to SARS-CoV infection, as demonstrated by Hoffmann et al, namely through the interaction of viral spike (S) protein with ACE2 receptors in the human body, so the inhibition of this interaction would be one of the therapeutic targets. Ho et al proved that emodin can inhibit the binding of the SARS-CoV S protein to ACE2 in vitro. The direct inhibition of S protein may also support the ACE2 cardioprotective function in patients with cardiovascular comorbidities. Emodin is also superior because it has various other benefits such as anti-inflammatory and immunosuppressive activity. Based on the research of Dong et al, emodin can be given orally but in combination with inhibitors of glucuronidation, metabolism can increase the bioavailability of this drug.Conclusion: Emodin has the potential to be developed for the effective therapy of COVID-19.